Intestinal mucosal microbiota composition of patients with acquired immune deficiency syndrome in Guangzhou, China - Xu, Haoming (Exp Ther Med, 2021)
Acquired immune deficiency syndrome, caused by the human immunodeficiency virus (HIV), has been associated with intestinal dysbiosis, which includes an increase in the number of mucosa-associated pathobionts. In the present study, the intestinal mucosal microbiota patterns of HIV-infected patients were compared with those of healthy individuals in a population from Guangzhou, China. The gut microbiota of intestinal mucosal samples from 12 patients with HIV (transmission routes included sex and intravenous drug abuse) was compared with that of 12 healthy age- and sex-matched controls. Gut microbial communities were profiled via sequencing of the bacterial 16S ribosomal RNA genes. Dysbiosis in HIV-infected individuals was characterized by decreased α-diversity, decreased levels of Firmicutes and increased levels of Proteobacteria. Furthermore, low mean counts of Lachnoclostridium, Roseburia, Thauera, Dorea and Roseburia inulinivorans, and high mean counts of Halomonas and Shewanella bacteria, were indicated to be HIV-associated mucosal bacterial alterations. The relative abundance of Fusobacterium and Lachnoclostridium was significantly decreased, while that of Halomonas and Shewanella was significantly increased in patients with sexually transmitted HIV-infection compared with healthy controls. Alterations of the gut microbiota during HIV infection were also indicated to be associated with the route of HIV transmission. Certain bacteria may be potential biomarkers for HIV infection in patients from Guangzhou, China.